The World Wide Telescope - Gray, Jim; Szalay, Alex (MSDN Magazine, 2006)
All astronomy data and literature will soon be online and accessible via the Internet. The community is building the Virtual Observatory, an organization of this worldwide data into a coherent whole that can be ac-cessed by anyone, in any form, from anywhere. The re-sulting system will dramatically improve our ability to do multi-spectral and temporal studies that integrate data from multiple instruments. The virtual observatory data also provides a wonderful base for teaching astronomy, scientific discovery, and computational science.